ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA PD TIMUR JAYA PONTIANAK - B51112071, TRI PUJI HIDAYATI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Companies need to implement a good strategy and optimal in order to compete with other companies. One of the strategies that can be used is to implement a system of internal control. Good internal control system will be able to assist in managing the company The main objective of this study was to determine how the system of internal control inventory Timur Jaya Pontianak PD, to determine the effectiveness of the internal control system inventory Timur Jaya Pontianak PD and to determine the factors that influence the effectiveness of the internal control system in PD Timur Jaya inventory of Pontianak. The technique of collecting data to be analyzed is by interview, observation, literature study, and questionnaires. This study uses three tools of analysis, organizational structure analysis, flowchart analysis, and analysis of internal control questionnaire. The results of this study indicate there are still some weaknesses in the inventory control system interenal Timur Jaya Pontianak PD. Some disadvantages and factors influencing the effectiveness of internal control systems in the inventory Timur Jaya Pontianak PD is going perangkapan task on human resources, procedures and policies that are less effective, inadequate data, and infrastructure is still lacking. It can be concluded internal control system inventory PD Timur Jaya Pontianak less effective. Keywords: Internal Control System, organizational structure, analysis flowcharts, internal control questionnaire analysis.